The role of mitochondrial ROS in the aging brain - Stefanatos, Rhoda; Sanz, Alberto (FEBS letters, 2018)
The brain is the most complex human organ, consuming more energy than any other tissue in proportion to its size. It relies heavily on mitochondria to produce energy and is made up of mitotic and postmitotic cells that need to closely coordinate their metabolism to maintain essential bodily functions. During aging, damaged mitochondria that produce less ATP and more reactive oxygen species (ROS) accumulate. The current consensus is that ROS cause oxidative stress, damaging mitochondria and resulting in an energetic crisis that triggers neurodegenerative diseases and accelerates aging. However, in model organisms, increasing mitochondrial ROS (mtROS) in the brain extends lifespan, suggesting that ROS may participate in signaling that protects the brain. Here, we summarize the mechanisms by which mtROS are produced at the molecular level, how different brain cells and regions produce different amounts of mtROS, and how mtROS levels change during aging. Finally, we critically discuss the possible roles of ROS in aging as signaling molecules and damaging agents, addressing whether age‐associated increases in mtROS are a cause or a consequence of aging.